Positive values in animation programs and methods of instilling them in children (Analytical study) - Rababah, Mohammad; Almarie, Rahma; Alsaleh, Maesa (Dirasat: Human and Social Sciences, 2022)
This study tended to analyze the positive values included in animation programs for children, and to explain the educational methods that were used to instill these positive values in children. The current study followed the descriptive and analytical approach, and in order to achieve the objectives of the study, a suitable analysis tool (the content analysis form) was built on which to analyze the content of the selected study sample specified in the two animation programs: “Abd al-Rahman's Diaries and Ahlam” and “Maktoob and Friends” program, with sixty episodes of the two programs. The study concluded with a number of results, the most important of which are: It was found that the two programs are meaningful and offer various positive values, in a variety of educational methods. There is an objective complementarity in employing the values of faith in the two programs, and the value of talent development / reading came to the highest rates of employment among the scientific values, and the educational methods in which the values are presented varied, including: the example method which was the most employed and used, and the method of persuasion obtained the highest percentage among the interactive methods The question / inquiry method ranked first among detection methods. The study recommends taking care to produce targeted programs that are loaded with positive values and for children, and the need to pay attention to the educational methods by which these values and contents are presented.